Peningkatan Kompetensi Guru dalam Menerapkan Model Pembelajaran melalui Supervisi Kelas di SDN 2 Bungtiang - Syamsiah, Syamsiah (Lembaga Yasin AlSys, 2022)
The purpose of this school action research (PTS) is to find out to what extent the supervision carried out by the school principal followed by the provision of guidance/treatment of target teachers can increase the competence of these teachers in applying learning models in class. In school action research (PTS) this was carried out in 2 cycles, the results of the actions taken proved to be able to increase teacher competence by achieving completeness standards. In the first cycle, the increase in teacher competence after class supervision was carried out after coaching on the use of several new learning models reached around 33.33% in cycle II, which could increase to 100%. The results of this school action research show that coaching school principals through academic supervision can improve teacher competence in applying learning models in their respective classes.